Effect of PBL with Prezi on critical thinking skills at SMAN 4 Pekanbaru - Nurhaliza Rahman; Mariani Natalina Linggasari; Riki Apriyandi Putra (Curricula: Journal of Curriculum Development, 2025)
This study aims to investigate the impact of Problem-Based Learning (PBL) supplemented by interactive Prezi media on students' critical thinking skills. The study was conducted in Class X of SMA Negeri 4 Pekanbaru in the second semester of April-June 2022/2023, using a quasi-experimental design with a pre-test-post-test control group. The parameter used was critical thinking ability, measured through five indicators, namely analysing, synthesising, identifying and solving problems, concluding, and evaluating. The post-test results showed an average score of 65.84 (moderately critical) in the control class, compared to 80.42 (critical) in the experimental class. The highest critical thinking performance was found in the analysis indicator, with a score of 66.67 (moderately critical) in the control class and 82.64 (critical) in the experimental class. The lowest performance was found in the evaluation indicator, with a score of 61.81 (less critical) in the control class and 77.08 (moderately critical) in the experimental class. The hypothesis test indicates that PBL supported by Prezi significantly influenced the critical thinking skills of Grade X students at SMAN 4 Pekanbaru.   Abstrak Penelitian ini bertujuan untuk mengetahui pengaruh Pembelajaran Berbasis Masalah (PBL) yang didukung media Prezi interaktif terhadap keterampilan berpikir kritis peserta didik. Penelitian dilakukan di Kelas X SMA Negeri 4 Pekanbaru pada semester dua April-Juni 2022/2023, menggunakan desain eksperimen semu dengan kelompok kontrol pretes-postes. Parameter yang digunakan adalah kemampuan berpikir kritis, diukur melalui lima indicator yaitu menganalisis, mensintesis, mengidentifikasi dan memecahkan masalah, menyimpulkan, dan mengevaluasi. Hasil postes menunjukkan skor rata-rata 65,84 (cukup kritis) pada kelas kontrol, dibandingkan dengan 80,42 (kritis) pada kelas eksperimen. Kinerja berpikir kritis tertinggi ditemukan pada indikator analisis, dengan skor 66,67 (cukup kritis) pada kelas kontrol dan 82,64 (kritis) pada kelas eksperimen. Kinerja terendah ditemukan pada indikator evaluasi, dengan skor 61,81 (kurang kritis) di kelas kontrol dan 77,08 (cukup kritis) di kelas eksperimen. Uji hipotesis menunjukkan bahwa PBL berbantuan Prezi secara signifikan memengaruhi keterampilan berpikir kritis peserta didik Kelas X di SMAN 4 Pekanbaru. Kata Kunci: berpikir kritis; media interaktif; pembelajaran berbasis masalah; Prezi